Síntese e caracterização de complexos de Cu(I), Cu(II) E Au(I) com ligantes triazenidos contendo substituintes triazóis - Morgan, Dieisson (2013)
Triazenido ions are isoelectronic to amidinato anions,[R'N C(R)=NR']- and have a broad versatility in coordination chemistry. Metal complexes including triazenido ligands find applications in various areas of chemistry. Triazenes and complexes including triazole derivatives show extensive applicability as for example in supramolecular chemistry and pharmacological compounds. This work presents deals with the study of new triazene derivatives with triazole substituents resulting from the click reactions, acting as ligands in complexes with Cu(I), Cu(II) and Au(I). The following ligands 1,3-bis(2-azidophenyl)triazene (2), 1-(methyl)-3-(2-(4-phenyl-1,2,3-triazole)triazene-N-oxide (4), 1-(phenyl)-3-(2-(4-phenyl-1,2,3-triazole)triazene (5), 1,3-bis(2-(4-phenyl-1,2,3-triazole)triazene (6) and, complexes 1,3-bis(2-azidophenyl)triazenide-κN11- triphenylphosphine-gold(I) (2a), bis-{1-(methyl)-3-[2-(4-phenyl-1,2,3-triazole-κN2)]triazenide-1-oxide-κ2N3,O}copper(II) (4b), 1-(phenyl)-3-(2-(4-phenyl-1,2,3-triazole)triazenide-κN- triphenylphosphine-κP-gold(I) (5a), 1,3-bis(2-(4-phenyl-1,2,3-triazole)triazenide-κN- triphenylphosphine-κP-gold(I) (6a), bis[1,3-bis(2-(4-phenyl-1,2,3-triazole-κN2)-μ-N3-triazenide]-κN11,κN13 copper(I)κN13,κN11´copper(I) (Cu Cu) (6b) were investigated. The compounds were characterized by IR, UV-Vis and NMR (1H e 13C) spectroscopy, low or high resolution mass spectrometry (EI, ESI, ESI(+)-TOF and ESI(-)-TOF) and X-ray diffraction on single crystal. Triazene (2) and complex (2a) exhibit intramolecular assembling through classical and non-classical hydrogen bonding. Complexes with Au(I), (2a), (5a) e (6a), the metal atom show linear coordination geometry. The metal atom in complex (6b) shows a T distorted coordination geometry, which is extended to a quadratic coordination resulting from d10 d10 interactions between Cu(I) ions. Triazene (6) and its respective complexes (6a) e (6b) exhibit intermolecular interactions of the type C−H···M. Antibacterial activity of triazene (5) and complex (5a) were assayed resulting to be inactive against the bacteria tested.